El Excentrico, 1949-09-01 - Garcia, Humberto:::Publisher:::::::::::: (Garcia Printing; San Jose, CA, 2023)
September 1949 [Septiembre de 1949] Ano 1, No. 4. Cover contains an interpretation of the novel, "Don Quixote De La Mancha", a widely translated and popular novel from the early seventeenth century. Below is a short summary and review of this novel from the book, "Cervantes."